2013
DOI: 10.1021/es304691a
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the Endocrine-Disrupting Potencies of Indoor Dust and Flame Retardants by Using Human Osteosarcoma (U2OS) Cell-Based Reporter Gene Assays

Abstract: Indoor dust is a sink for many kinds of pollutants, including flame retardants (FRs), plasticizers, and their contaminants and degradation products. These pollutants can be migrated to indoor dust from household items such as televisions and computers. To reveal high-priority end points of and contaminant candidates in indoor dust, using CALUX reporter gene assays based on human osteosarcoma (U2OS) cell lines, we evaluated and characterized the endocrine-disrupting potencies of crude extracts of indoor dust co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 55 publications
11
69
1
Order By: Relevance
“…The 4-and 5-ring benz[a]anthracene and benzo[k]fluoranthene were principal AhR agonist activity contributors owing to their higher TEFs (7 and 11, respectively). Nonetheless, 9 AhR agonistic PAHs only accounted for a small portion of the AhR agonist activities in indoor dust (2.1-6.2%), which were similar to other studies (Louiz et al, 2008;Muusse et al, 2012;Tue et al, 2013). Our results indicated that further investigation is necessary to identify unknown xenobiotic AhR agonist contaminants in indoor dust from Taiwan.…”
Section: Contributions Of Pahs To the Ahr Agonist Activity In Indoor supporting
confidence: 88%
See 3 more Smart Citations
“…The 4-and 5-ring benz[a]anthracene and benzo[k]fluoranthene were principal AhR agonist activity contributors owing to their higher TEFs (7 and 11, respectively). Nonetheless, 9 AhR agonistic PAHs only accounted for a small portion of the AhR agonist activities in indoor dust (2.1-6.2%), which were similar to other studies (Louiz et al, 2008;Muusse et al, 2012;Tue et al, 2013). Our results indicated that further investigation is necessary to identify unknown xenobiotic AhR agonist contaminants in indoor dust from Taiwan.…”
Section: Contributions Of Pahs To the Ahr Agonist Activity In Indoor supporting
confidence: 88%
“…Higher AhR agonist activities were detected in the indoor dust samples collected from computer room (16112 ng BaP EQ/g dust dry weight (dw)) and laboratory (9686 ng BaP EQ/g dust dw), which were further fractionated by HPLC to isolate active HPLC fractions. The AhR agonist activities in Taiwanese indoor dust (3448-16112 ng BaP EQ/g dust dw) were similar to or greater than those detected in indoor dust from New York State (30-8000 pg TCDD EQ/g, equivalent to 67-17778 ng BaP EQ/g) and Japan (38-1400 pg TCDD EQ/g, equivalent to 84-3111 ng BaP EQ/g), but lower than those in street dust collected from Vietnam and India (11-68 ng TCDD EQ/g, equivalent to 24-151 µg BaP EQ/g) using DR-CALUX assay (Suzuki et al, 2007;Tue et al, 2013;Tuyen et al, 2014). The variations in AhR agonist activities suggested area-specific sources of AhR agonist contaminants in different regions.…”
Section: Ahr Agonist Activity In Indoor and Outdoor Dust Samplesmentioning
confidence: 95%
See 2 more Smart Citations
“…The assay procedure has been described previously (Suzuki et al, 2013). Briefly, GR-CALUX cells were cultured at 37°C under 5% CO 2 and high humidity in DF (1:1 mixture of Dulbecco's Modified Eagle's Medium and Ham's F12 [DMEM-F12]) medium supplemented with 7.5% fetal calf serum (FCS).…”
Section: Agonistic Testing With the Gr-calux Assaymentioning
confidence: 99%